Accessibility of facilities in selected restaurants along Tomas Morato Avenue - Chan, Jehan I.; Mayo, Adelaida Villaraza (2009.)
The study assessed the accessibility of facilities in fourteen selected restaurants located along Tomas Morato Avenue using a descriptive research design, specifically a case study. The existing facilities were evaluated in terms of design features based on the National Building Code accessibility requirements namely ramp, entrance door, corridor, public toilet, signage and floor. The sampling design for the study involved two stages as follows: 1.) Of all the restaurants along Tomas Morato Avenue, thirty-six restaurants that offer table service were identified. 2.) From among the thirty-six restaurants, fifteen were randomly selected. An accessibility checklist based on the National Building Code accessibility requirements was used as the major data gathering instrument in the study. There were twenty-four accessibility requirements included in the accessibility checklist categorized under the six design features mentioned. Content analysis was used to analyze the data to determine the level of compliance to Accessibility Law (Republic Act 344) "an Act to enhance the Mobility of Disabled Persons by requiring certain buildings, institutions, establishments and public utilities to install access facilities and other devices." applied in the selected restaurants. Results revealed that majority of the existing facilities in the selected restaurants were not in accordance to National Building Code accessibility requirements. None of the fourteen selected restaurants fully complied with the Accessibility Law. Furthermore, none of the restaurants met all the twenty-four accessibility requirements in the checklist. Majority of the restaurants met less than 50% of the total requirements. Only 5 out of the 14 restaurants complied with at least 50% of the total requirements. The findings inferred that the level of compliance to Accessibility Law is significantly low. The results of this study therefore suggest that full compliance to the Accessibility Law is still a prevailing access issue and that most of the provisions of the law are not enforced. Therefore, it is highly recommended that this study be replicated in a larger scale. Future research to determine the reasons for limited access by people with disabilities in many private and public facilities is also recommended.
Thesis (BS Interior Design)--University of the Philippines Diliman.
Keywords: Restaurants -- Philippines -- Accessibility